VARIASI DOSIS PENAMBAHAN PAC-R TERHADAP SIFAT FISIK LUMPUR PEMBORAN YANG TERKONTAMINASI GYPSUM - Sanjaya, Muhammad Diki (INFO-TEKNIK, 2025)
ABSTRACT One of Drilling is a critical process in oil and gas exploration and production, with its success highly dependent on the performance of drilling mud. Drilling mud serves essential functions such as maintaining wellbore stability, cooling the drill bit, and transporting cuttings to the surface. However, in field applications, the mud is often contaminated by formation materials, including gypsum. Gypsum contamination can negatively affect the physical properties of the mud, such as increasing filtrate volume and decreasing pH, which can reduce operational efficiency, compromise safety, and increase the risk of equipment damage.This study investigates the effect of adding PAC-R additive at concentrations of 0.25%, 0.5%, and 1% to water-based mud contaminated with 3% gypsum. The evaluation focused on key mud properties, including mud weight, plastic viscosity, yield point, gel strength, filtrate volume, and pH. The presence of 3% gypsum decreased the initial pH from 11 to 7.49 and increased the filtrate volume from 8 mL to 11 ml. The addition of 0.25% PAC-R to the contaminated mud raised the pH to 10.5, 0.5% PAC-R increased the pH to 10.8, while 1% PAC-R slightly reduced the pH to 10.2. These results indicate that PAC-R additive can help mitigate the adverse effects of gypsum contamination and improve the mud's physical properties. Keywords: gypsum contamination, plastic viscosity, yield point, gel strength, filtration loss.